A systems analysis of inter-annual changes in the pattern of sheep flock productivity in Tanzanian livestock research centres - Rey, B.; Das, S.M. (Elsevier, 1997)
Annual estimates of production traits over a 22 year period (1965-1987) for Black Head Persian sheep (BHP) from Malya and West Kilimanjaro research centers in Tanzania were utilized to analyse variation of flock productivity over time. Principal component analysis was used to anlyse the variation of flock productivity over time. Principal component analysis indicated major trends in the variation of trait combinations, while cluster analysis was used to identify years with similar patterns in the combination of traits. The paper discusses the historical pattern, which is identified. It appears that productivity patterns were only weakly related to ecological changes, but were more strongly related to management factors. The approach and analytical technique employed are recommended as tools in livestock systems diagnostic research.